TEACHER’S CREATIVITY IN ELT DURING PANDEMIC COVID-19 PHASE AT SMA NEGERI 1 TORAJA UTARA - Matius Tandikombong; Rigel Sampelolo (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
The objective of this research was to find out of the teacher’s creativities on ELT during the pandemic covid-19 at SMA Negeri 1 Toraja Utara. This research is qualitative and the subjects were the english teacher at SMA Negeri 1 Toraja Utara. The researcher collected the data by interviewing the participants of this research. Next, the writer analyzed the data obtained to find out some creativities in ELT by the English teachers at SMA Negeri 1 Toraja Utara based on the five categories those are : 1) Conveyed in presentation of lesson. 2) Creativity in giving assignments. 3) Creativity in teacher. 4) learner interaction. 4) Creativity in teacher characteristics. The result of the research of the research showed that the teachers used several applications to applied five categories of teacher’ creativities above, those are: WhatSapp, Google meet, Zoom meeting, Google classroom besides that the teacher also made tutorial video to do a assignment.